Hydrophobic Magnetic Nanoparticle Assisted One‐Pot Liquid‐Phase Peptide Synthesis. Issue 40 (14th August 2017) - Okada, Yohei; Asama, Hitomi; Wakamatsu, Hiroki; Chiba, Kazuhiro; Kamiya, Hidehiro
Abstract : Chemically stable hydrophobic magnetic nanoparticles were prepared by using an isocyanate as an anchoring group and were applied to the soluble tag‐assisted liquid‐phase peptide synthesis of the peptide elastin. Couplings and deprotections were effectively performed in the presence of the nanoparticles, and the desired product was rapidly collected as a "magnetic" precipitate, enabling a one‐pot procedure. Sonication of the nanoparticles significantly suppressed gelation of the reaction mixture, which allowed the highly aggregating elastin peptide to be synthesized in one pot without difficulty. Abstract : Chemically stable, hydrophobic, magnetic nanoparticles are prepared by using an isocyanate as an anchoring group and are applied to the soluble tag‐assisted liquid‐phase peptide synthesis of elastin. Couplings and deprotections are effectively performed in the presence of the nanoparticles, and the desired product is rapidly collected as a "magnetic" precipitate, enabling a one‐pot procedure.